Pengembangan LKPD Menggunakan Model Discovery Learning untuk Meningkatkan Pemahaman Konsep Siswa Mata Pelajaran Sosiologi Kelas X SMAN 1 Suliki - Fatimah Az Zahra; Erianjoni Erianjoni (Naradidik: Journal of Education and Pedagogy, 2022)
This study aims to improve the understanding of the concepst of student in class X SMA through the development of student worksheets using an discovery learning model. This research is motivated because of the low concept of student from the material forms of social interactio. So a method is needed to overcome this problem. One of which is by using the discovery learning model. This type of research is research and devolopment. The development model is 4 D. Data collection techniques use research instrumens consisting of validation practicality and effectivenness of. This research was conducted on students of class x SMA Negeri 1 Suliki by obtaining productvalidity result in the high category. The product practicality test was carried out by distributing questionnaires to student by obtaining result in the practical category, the result of the study concluded tha the LKPD discovery learning model is feasible to use and can help improve the understanding of the concept of class x students.